Diagnóstico de salud bucodental y factores de riesgo en los centros educativos primarios Josefa Amelia Ortega y Santa Catalina de la parroquia rural San Lucas del cantón Loja año 2013. - Cuenca Espinoza, Jhandry Agustin (2013)
Dental caries and periodontal disease are considered , the most prevalent oral diseases worldwide, so it is necessary to identify the risk factors , the causality of these and their relation to these diseases . The objectives of this research work were, diagnose oral pathologies present, its prevalence and risk factors associated with these diseases, in school students: "Josefa Ortega Amelia " and " Santa Catalina” in theparish of San Lucas, year 2013. We designed a quantitative, descriptive and prospective. The study area encompassed the 100 % of the population of the 2 aforementioned educational institutions, consisting of 211 students. Oral examination was performed at each of the patients in their educational establishments. Data were recorded in dental history. A survey with closed questions about oral hygiene, eating habits and oral care. Processed and analyzed the data collected, the results show that: the oral health of this population is affected due to several indicators negatively involved in oral health, and lack of dental education, oral health promotion and prevention, little interest and ignorance of the population, about the importance of oral cleanliness. The most prevalent oral diseases are: dental caries appearing in 88.6% of the total population, gingival inflammation in 69.2 %, and thepresence of malocclusionsby 34.4 %. Keywords: caries, dental fluorosis, riskfactors, gingival inflammation, oral health.